Ultrasonido a pie de cama para diagnóstico y drenaje percutáneo de absceso hepático piógeno en choque séptico: Reporte de caso en entorno de recursos limitados - Fausto Maldonado Coronel; Katherine Maldonado Coronel; Cristina Muñoz Lalangui; Oswaldo Bolaños Ladinez; Paula Olivos Massa (Critical Care & Emergency Medicine, 2026)
Abstract: Point-of-care ultrasound has revolutionized medical practice, offering personalized treatment, diagnostic accuracy, continuous monitoring with follow-up interventions, and enhanced patient safety. We report the case of a 47-year-old woman admitted with abdominal pain, progressive hemodynamic deterioration, multiple organ failure, and septic shock with elevated acute-phase reactants. Point-of-care ultrasound was performed to identify the source of infection, revealing multiple liver abscesses. Given the limited resources available due to the lack of interventional radiology, drainage was performed by an intensivist trained in ultrasound using an ultraportable pocket-sized unit and a central venous catheter as the only therapeutic option for controlling the infectious focus in a life-threatening situation. The collection was drained, resulting in improvement of organ function and discharge. Point-of-care ultrasound enabled the identification and control of the infectious focus in a patient with septic shock, becoming the primary diagnostic and therapeutic tool in a resource-limited setting. It is now common knowledge that the applicability of personalized bedside ultrasound can prevent catastrophic events in various medical emergencies.